Standard fluorescent imaging of live cells is highly genotoxic. Issue 6 (6th May 2013) - Ge, Jing; Wood, David K.; Weingeist, David M.; Prasongtanakij, Somsak; Navasumrit, Panida; Ruchirawat, Mathuros; Engelward, Bevin P.
Abstract: Fluorescence microscopy is commonly used for imaging live mammalian cells. Here, we describe studies aimed at revealing the potential genotoxic effects of standard fluorescence microscopy. To assess DNA damage, a high throughput platform for single cell gel electrophoresis is used (e.g., the CometChip). Light emitted by three standard filters was studied: (a) violet light [340–380 nm], used to excite DAPI and other blue fluorophores, (b) blue light [460–500 nm] commonly used to image green fluorescent protein (GFP) and Calcein AM, and (c) green light [528–553 nm], useful for imaging red fluorophores. Results show that exposure of samples to light during imaging is indeed genotoxic even when the selected wavelengths are outside the range known to induce significant damage levels. Shorter excitation wavelengths and longer irradiation times lead to higher levels of DNA damage. We have also measured DNA damage in cells expressing enhanced GFP or stained with Calcein AM, a widely used green fluorophore. Data show that Calcein AM leads to a synergistic increase in the levels of DNA damage and that even cells that are not being directly imaged sustain significant DNA damage from exposure to indirect light. The nature of light‐induced DNA damage during imaging was assessed using the Fpg glycosylase, an enzyme that enables quantification of oxidative DNA damage. Oxidative damage was evident in cells exposed to violet light. Furthermore, the Fpg glycosylase revealed the presence of oxidative DNA damage in blue‐light exposed cells for which DNA damage was not detected using standard analysis conditions. Taken together, the results of these studies call attention to the potential confounding effects of DNA damage induced by standard imaging conditions, and identify wavelength, exposure time, and fluorophore as parameters that can be modulated to reduce light‐induced DNA damage. © 2013 International Society for Advancement of Cytometry